Colloidal TiO2 Nanoparticles Synthesized via Pulsed Laser Ablation in Liquid for Photocatalytic Degradation of Rhodamine B - Nafaul Mubarokah; Ali Khumaeni; Iis Nurhasanah (Journal of Physics and Its Applications, 2026)
Colloidal TiO2 nanoparticles were synthesized via pulsed laser ablation in liquid (PLAL) method using a Q-switched Nd:YAG laser operating at 1064 nm. The optical and structural properties were analyzed using UV-Vis spectroscopy, X-ray diffraction (XRD), transmission electron microscopy (TEM), and selected area diffraction (SAED). The amorphous TiO2 colloids exhibited a distinct absorption edge in the UV region, with the optical bandgap (Eg) estimated by the Tauc plot to be approximately 3.75 eV. Photocatalytic activity was evaluated through the degradation of Rhodamine B (10 ppm) under UV lamp (254 nm) irradiation. The TiO2 photocatalyst achieved more than 75% degradation within 150 minutes, whereas the control (photolysis without catalyst) showed less than 5% degradation. These results demonstrate that PLAL enables a clean and straightforward synthesis of high-purity amorphous TiO2 nanoparticles with effective photocatalytic activity under UV irradiation.